THU0153 PATTERNS OF SUSTAINED REMISSION AND SUBSEQUENT DMARD TAPERING IN EARLY RHEUMATOID ARTHRITIS: DATA FROM THE CANADIAN EARLY ARTHRITIS COHORT. (June 2019) - Powell, Maria; Bykerk, Vivian; Schieir, Orit; Pope, Janet; Bartlett, Susan J.; Bessette, Louis; Boire, Gilles; Hitchon, Carol; Keystone, Edward; Thorne, Carter; Tin, Diane; Valois, Marie-France; et al.
Abstract : Background: Rheumatoid arthritis (RA) treatment emphasizes aggressive titration of disease-modifying antirheumatic drugs (DMARDs) with the goal of achieving disease remission. This often includes the use of multiple DMARDs in combination, which can have a significant impact on patients' lives and add costs to the healthcare system. Objectives: To describe the patterns of sustained remission and subsequent treatment reduction in usual clinical practice for patients with early RA. Methods: Patients (age >18) enrolled in the Canadian early ArThritis CoHort (CATCH) between January 2007 to March 2017 were analyzed. CATCH is a prospective, observational study of patients with early inflammatory arthritis (symptoms <1 year) treated in rheumatology clinics across Canada. The analysis cohort included patients with a diagnosis of RA according to the 1987 or 2010 ACR/EULAR classification criteria, active disease at enrolment (DAS28>2.6) and those treated with at least one DMARD or biologic agent within the first three months of study enrolment. We defined sustained remission as achieving a DAS28 < 2.6 at two consecutive follow-up visits at least six months apart. Reduction of therapy was defined as a minimum of a 25% dose reduction of conventional synthetic, targeted or biologic DMARDs. Descriptive statistics were used to summarize the time to remission and reductions in DMARD therapy. Results: Eight hundred and thirty-seven (40%) of the 2, 097 eligible patients achieved sustained remission during the study period. Of these, 60% did so within the first 18 months and 92% within the first four years (Figure 1 ). The mean (SD) baseline DAS28 was 5.1 (1.3), and HAQ-DI was 1.0 (0.7). At the time of remission, 80% were prescribed methotrexate (55% subcutaneously), 71% were prescribed combination therapy with other conventional synthetic DMARDs, and 13% were prescribed a biologic agent. In the year after attaining sustained remission, 327 (39%) patients reduced treatment in the following pattern (patients may have had more than one change): 250 patients (30%) reduced or stopped methotrexate, 196 patients (23%) reduced or stopped non-methotrexate DMARDs, and 34 patients (4%) reduced or stopped biologic agents. Of those that reduced or stopped a biologic, only one was due to side effects. For the 250 patients who reduced or stopped methotrexate, 25 were for a side effect. Conclusion: Achieving sustained remission occurred in 40% of early RA patients in usual clinical practice. Treatment reductions following sustained remission occurred in over a third of patients over the next 12 months, and consisted mainly of adjustment in non-biologic DMARDs. Disclosure of Interests: Maria Powell: None declared, Vivian Bykerk Grant/research support from: Mallinckrodt, BMS, Crescendo Biosciences, Sanofi/Regeneron., Consultant for: Amgen, Pfizer, UCB, Scipher, Sanofi/Genzyme/Regeneron, Orit Schieir: None declared, Janet Pope Consultant for: Eli Lilly and Company, Susan J. Bartlett Consultant for: Pfizer, UCB, Lilly, Novartis, Merck, Jansen, Abbvie, Louis Bessette Grant/research support from: Amgen, BMS, Janssen, Roche, UCB, AbbVie, Pfizer, Merck, Celgene, Sanofi, Lilly, Novartis, Consultant for: Amgen, BMS, Janssen, Roche, UCB, AbbVie, Pfizer, Merck, Celgene, Sanofi, Lilly, Novartis, Speakers bureau: Amgen, BMS, Janssen, Roche, UCB, AbbVie, Pfizer, Merck, Celgene, Sanofi, Lilly, Novartis, Gilles Boire Grant/research support from: Investigator-initiated studies: Amgen, Abbvie, BMS, Eli Lilly, Merck, Novartis, Pfizer, Consultant for: Advisory boards: Amgen, BMS, Celgene, Eli Lilly, Pfizer, Speakers bureau: Merck, BMS, Pfizer, CArol Hitchon Grant/research support from: Pfizer, UCB (unrelated studies), Edward Keystone Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, F. Hoffmann-La Roche Inc, Gilead, Janssen Inc, Lilly Pharmaceuticals, Pfizer Pharmaceuticals, Sanofi-Aventis, Consultant for: AbbVie, Amgen, AstraZeneca Pharma, Biotest, Bristol-Myers Squibb Company, Celltrion, Crescendo Bioscience, F. Hoffmann-La Roche Inc, Genentech Inc, Gilead, Janssen Inc, Lilly Pharmaceuticals, Merck, Pfizer Pharmaceuticals, Sandoz, UCB., Speakers bureau: Amgen, AbbVie, Bristol-Myers Squibb Canada, F. Hoffmann-La Roche Inc., Janssen Inc., Merck, Pfizer Pharmaceuticals, Sanofi Genzyme, UCB, Carter Thorne Grant/research support from: Investigator-initiated studies: Amgen, Pfizer. RCTs: Abbvie, Celgene, CaREBiodam, Novartis, Pfizer, Consultant for: Advisory board: Abbvie, Amgen, Celgene, Lilly, Medexus/Medac, Merck, Novartis, Pfizer, Sanofi. Consultant: Abbvie, Centocor, Janssen, Lilly, Medexus/Medac, Pfizer, Speakers bureau: Medexus/Medac, Diane Tin: None declared, Marie-France Valois: None declared, Glen Hazlewood : None declared